Aliado - a design concept of AI for decision support in oncological liver surgery - Schulze, André; Haselbeck-Köbler, Michael; Brandenburg, Jonas Maurice; Daum, Marie T. J.; März, Keno; Hornburg, S.; Maurer, H.; Myers, F.; Reichert, G.; Bodenstedt, Sebastian; Nickel, Felix; Kriegsmann, Mark; et al. (European journal of surgical oncology, 2025)
Background - The interest in artificial intelligence (AI) is increasing. Systematic reviews suggest that there are many machine learning algorithms in surgery, however, only a minority of the studies integrate AI applications in clinical workflows. Our objective was to design and evaluate a concept to use different kinds of AI for decision support in oncological liver surgery along the treatment path. - Methods - In an exploratory co-creation between design experts, surgeons, and data scientists, pain points along the treatment path were identified. Potential designs for AI-assisted solutions were developed and iteratively refined. Finally, an evaluation of the design concept was performed with n = 20 surgeons to get feedback on the different functionalities and evaluate the usability with the System Usability Scale (SUS). Participating surgeons had a mean of 14.0 ± 5.0 years of experience after graduation. - Results - The design concept was named “Aliado”. Five different scenarios were identified where AI could support surgeons. Mean score of SUS was 68.2 ( ± 13.6 SD). The highest valued functionalities were “individualized prediction of survival, short-term mortality and morbidity”, and “individualized recommendation of surgical strategy”. - Conclusion - Aliado is a design prototype that shows how AI could be integrated into the clinical workflow. Even without a fleshed out user interface, the SUS already yielded borderline good results. Expert surgeons rated the functionalities favorably, and most of them expressed their willingness to work with a similar application in the future. Thus, Aliado can serve as a surgical vision of how an ideal AI-based assistance could look like.